2020
DOI: 10.1002/star.202000094
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonication Improves the Structures and Physicochemical Properties of Cassava Starch Films Containing Acetic Acid

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…In contrast, the AFM image of the films processed with ultrasonication (Figure 3b,d) shows that the surfaces are relatively smooth, compact, and homogeneous, which indicated that TP was well-distributed in the PVA-HC matrix, and that no critical agglomeration of TP was visible. A similar result was reported by Wu and coauthors, who observed that the untreated film surface was rough, while the surfaces of the films processed with ultrasonication were smooth and cohesive [41]. In this study, due to the disintegration of the TP agglomeration under intense ultrasonics in the film-forming solution, the film-forming components could be completely solubilized and hydrated, resulting in more homogeneous PVA-HC/TP film structure [42].…”
Section: Microstructure Analysissupporting
confidence: 88%
“…In contrast, the AFM image of the films processed with ultrasonication (Figure 3b,d) shows that the surfaces are relatively smooth, compact, and homogeneous, which indicated that TP was well-distributed in the PVA-HC matrix, and that no critical agglomeration of TP was visible. A similar result was reported by Wu and coauthors, who observed that the untreated film surface was rough, while the surfaces of the films processed with ultrasonication were smooth and cohesive [41]. In this study, due to the disintegration of the TP agglomeration under intense ultrasonics in the film-forming solution, the film-forming components could be completely solubilized and hydrated, resulting in more homogeneous PVA-HC/TP film structure [42].…”
Section: Microstructure Analysissupporting
confidence: 88%
“…It was found that high ultrasonic energy may degrade the starch chain and weaken the starch chain interaction, resulting in an increasing in the brittleness of the material. [ 27 ] Insoluble particles were elastic structures that made the starch film mechanically stable. [ 22 ] It was adverse to the mechanical properties of the film when high ultrasonic power and long duration time caused all or most of the destruction of insoluble particles.…”
Section: Resultsmentioning
confidence: 99%
“…The band at 1149 cm -1 is due to C-O-C asymmetric stretch vibration. Further, the presence of absorption bands at around 1020 and 848 cm -1 in the two spectra indicated that both films possess C-O and C-O-C functional groups, respectively (Wua et al, 2021). FTIR spectra of C.St and SVG/C.St films are almost identical and show characteristic peaks corresponding to starch molecules (Figure 1).…”
Section: Ftir Analysismentioning
confidence: 93%